Segmental Analysis of English and Arabic Vowels - Dr. Dalal Alfadhil Attaher Salheen (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2024)
When learning another language, learners must consider various factors that can either support or conflict with the learning process. Regarding the sound system, particularly the differences between English and Arabic, Arabic learners face challenges as some sounds in English do not exist in Arabic, and vice versa. Notably, the vowel systems of the two languages differ significantly, and this discrepancy needs to be recognized and addressed by Arabic learners of English. This paper studies the vowel sounds of English and Arabic, highlighting the equivalents between the two languages. Based on the existing literature, there is a great difference between vowels in English and Arabic. The difference lies in quality and in quantity, as each language has its distinctive features of articulation. This paper suggests that Arabic learners of English must consider the differences at the early stages of language learning, as this would improve their perception and production of sounds. Subsequently, communication would be more effective, which is the goal that drives all language learners from the very start.